Effect of different concentrations of pyrethroid and organophosphorus pesticides on seedling growth of Cicer arietinum: Effect of pesticide concentration on Cicer arietinum (SAARC Journal of Agriculture, 2022)
Seed treatment with pesticides is one of the components of IPM. Pesticides, the chemical ingredients are generally used to assassinate biological entities that cause damage to cultivated crops. To maintain the quantity and quality of the plant produce, a large number of chemicals in the form of pesticides and/or fungicides are sprayed on them.  Although these compounds affect the growth of seedlings and also negatively influence the growth of symbiotic bacteria and their interaction with crop plants resulting in a reduction in nitrogen fixation by plants and ultimately yield. A study on the consequences of chemical pesticides on seed germination and seedling growth of Cicer arietinum was carried out at Chhatrapati Shahu Ji Maharaj University, Kanpur, Uttar Pradesh, India in 2016. The present study was done to assess the effect of pesticides on root length, shoot length, leaf area, fresh weight, and dry weight of seedlings. The experiment was conducted by using different concentrations viz., 0% (control), 0.5%, 1%, 1.5%, 2%, 2.5%, 5%, 7.5%, and 10% of organophosphorus monocrotophos and pyrethroid pesticide deltamethrin. Observations were done on the 7th, 14th, and 21st days of radicle emergence. The study showed that both types of pesticides such as pyrethroid deltamethrin and organophosphorus monocrotophos were found to be toxic to plants in high concentrations and can be preferred in low concentrations only like 0.5%, which is less harmful to crop plants.SAARC J. Agric., 20(1): 55-65 (2022)